Elucidating the mechanism of the CO2 methanation reaction over Ni–Fe hydrotalcite-derived catalysts via surface-sensitive in situ XPS and NEXAFS. Issue 34 (24th April 2020) - Giorgianni, Gianfranco; Mebrahtu, Chalachew; Schuster, Manfred Erwin; Large, Alexander Ian; Held, Georg; Ferrer, Pilar; Venturini, Federica; Grinter, David; Palkovits, Regina; Perathoner, Siglinda; Centi, Gabriele; Abate, Salvatore; et al.
Abstract : In situ surface sensitive XPS and NEXAFS clarify the promotion effect of Fe in Ni–Fe/hydrotalcite-derived catalysts for the CO2 methanation reaction. Abstract : Hydrotalcite-derived Ni and Fe-promoted hydrotalcite-derived Ni catalysts were found to outperform industrial catalysts in the CO2 methanation reaction, however the origin of the improved activity and selectivity of these catalysts is not clear. Here, we report a study of these systems by means of in situ X-ray photoelectron spectroscopy and near-edge X-ray absorption spectroscopy elucidating the chemical nature of the catalysts surface under reaction conditions and revealing the mechanism by which Fe promotes activity and selectivity towards methane. We show that the increase of the conversion leads to hydroxylation of the Ni surface following the formation of water during the reaction. This excessive Ni surface hydroxylation has however a detrimental effect as shown by a controlled study. A dominant metallic Ni surface exists in conditions of higher selectivity towards methane whereas if an increase of the Ni surface hydroxylation occurs, a higher selectivity towards carbon monoxide is observed. The electronic structure analysis of the Fe species under reaction conditions reveals the existence of predominantly Fe(iii ) species at the surface, whereas a mixture of Fe(ii )/Fe(iii ) species is present underneath the surface when selectivity to methane is high. Our results highlight that Fe(ii ) exerts a beneficial effect on maintaining Ni in a metallic state, whereas the extension of the Fe oxidation is accompanied by a more extended Ni surface hydroxylation with a negative impact on the selectivity towards methane.